2020
DOI: 10.3390/ijms21072584
|View full text |Cite
|
Sign up to set email alerts
|

Effective MSTN Gene Knockout by AdV-Delivered CRISPR/Cas9 in Postnatal Chick Leg Muscle

Abstract: Muscle growth and development are important aspects of chicken meat production, but the underlying regulatory mechanisms remain unclear and need further exploration. CRISPR has been used for gene editing to study gene function in mice, but less has been done in chick muscles. To verify whether postnatal gene editing could be achieved in chick muscles and determine the transcriptomic changes, we knocked out Myostatin (MSTN), a potential inhibitor of muscle growth and development, in chicks and performed transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The destruction of the RING domain in RNF114 may result in its degradation because the key domains are important to protein stability (Heessen et al, 2005;Liu et al, 2017). The instability of mutant mRNA was unexpected, although the degradation of mutant mRNA had been previously demonstrated in some gene-edited animals (Oo et al, 2020;Xu et al, 2020). The female mice were completely sterile after Rnf114 editing.…”
Section: Discussionmentioning
confidence: 97%
“…The destruction of the RING domain in RNF114 may result in its degradation because the key domains are important to protein stability (Heessen et al, 2005;Liu et al, 2017). The instability of mutant mRNA was unexpected, although the degradation of mutant mRNA had been previously demonstrated in some gene-edited animals (Oo et al, 2020;Xu et al, 2020). The female mice were completely sterile after Rnf114 editing.…”
Section: Discussionmentioning
confidence: 97%
“…Studies to date have examined the gain and loss‐of‐function of MSTN in chicken embryos, the consequences for the muscle progenitor population, and the association between MSTN SNPs and broiler performance 39,40 . We did not further analyze the our MSTN genome‐modified chickens in detail, but recent studies showed that mutation of MSTN in chicken 41 and quail has an anti‐myogenic effect 42 ; moreover, spatial MSTN mutations introduced by adenoviral CRISPR‐Cas9 induce differential gene expression involved in cell differentiation, muscle growth and development, and energy metabolism in postnatal chicken 43 . Therefore, we expect that these animals will exhibit elevated protein synthesis capacity as well as improved muscle cell development.…”
Section: Discussionmentioning
confidence: 99%
“…These results are important because the germline chimera efficiency is higher than those of other PGC-free methods, and the method has the potential to be broadly applied across poultry species. Additionally, adenovirus can be applied to postnatal gene editing in poultry [ 67 ]. Xu et al adenoviral vector expressing MSTN gene-targeting sgRNA and SpCas9 was injected into the chick leg muscle, resulting in successful knockout of MSTN in that tissue.…”
Section: Crispr-cas9 Mediated Genome Editing In Poultrymentioning
confidence: 99%